A preliminary checklist of fish species in the peat swamp forest of Ayer Hitam Utara State Park Forest, Johor, Malaysia - Fahmi-Ahmad, Muhammad; Abdullah Halim, Muhammad Rasul; Ilham-Norhakim, Mohd Lokman; Azam Arshad, Muhammad Nur; Zakaria, Zahar Azuar; A. Ghani, Intan Faraha; Aqmal-Naser, Mohamad; Mustafa, Siti Noratikah; Abdul-Latiff, Muhammad Abu Bakar; Azmai Amal, Mohammad Noor; B. Ahmad, Amirrudin; Md Zain, Khaironizam (Universiti Putra Malaysia, 2024)
Ayer Hitam Utara State Park Forest (AHUSPF) is an invaluable sanctuary in Johor, the last remaining intact peat swamp forest reserve that hosts many species unique to this distinctive habitat. Some rapid surveys conducted from 2019 to 2022 recorded 40 species of freshwater fish within AHUSPF. Notably, 11 are stenotopic to acid blackwater, and 12 are stenotopic to acid water, most belonging to the family Osphronemidae and Danionidae. The International Union for Conservation of Nature Red List has designated two species, Encheloclarias curtisoma and Betta persephone, as Endangered, while Betta omega is classified as Critically Endangered. The checklist presented herein was first produced from an inventory study in AHUSPF. The preservation of peat swamp forests in the area is under imminent threat due to the alarming rate of land conversion, forest fires, and the recent potential threat from the red-claw crayfish invasion in the aquatic environment. Hence, continuous monitoring is vital for documenting and updating the conservation status of the fish species. These endeavours will facilitate the development of practical conservation approaches to ensure the long-term sustainability of AHUSPF and its associated species.